Microplastic pollution is widely detected in US municipal wastewater treatment plant effluent. (November 2016) - Mason, Sherri A.; Garneau, Danielle; Sutton, Rebecca; Chu, Yvonne; Ehmann, Karyn; Barnes, Jason; Fink, Parker; Papazissimos, Daniel; Rogers, Darrin L.
Abstract: Municipal wastewater effluent has been proposed as one pathway for microplastics to enter the aquatic environment. Here we present a broad study of municipal wastewater treatment plant effluent as a pathway for microplastic pollution to enter receiving waters. A total of 90 samples were analyzed from 17 different facilities across the United States. Averaging all facilities and sampling dates, 0.05 ± 0.024 microparticles were found per liter of effluent. Though a small value on a per liter basis, even minor municipal wastewater treatment facilities process millions of liters of wastewater each day, yielding daily discharges that ranged from ∼50, 000 up to nearly 15 million particles. Averaging across the 17 facilities tested, our results indicate that wastewater treatment facilities are releasing over 4 million microparticles per facility per day. Fibers and fragments were found to be the most common type of particle within the effluent; however, some fibers may be derived from non-plastic sources. Considerable inter- and intra-facility variation in discharge concentrations, as well as the relative proportions of particle types, was observed. Statistical analysis suggested facilities serving larger populations discharged more particles. Results did not suggest tertiary filtration treatments were an effective means of reducing discharge. Assuming that fragments and pellets found in the effluent arise from the 'microbeads' found in many cosmetics and personal care products, it is estimated that between 3 and 23 billion (with an average of 13 billion) of these microplastic particles are being released into US waterways every day via municipal wastewater. This estimate can be used to evaluate the contribution of microbeads to microplastic pollution relative to other sources (e.g., plastic litter and debris) and pathways (e.g., stormwater) of discharge. Graphical abstract: Abstract : Municipal wastewater treatment facilities are releasing over 4 million microplastic particles per facility per day into US waterways with fibers and fragments being the most common type.